Peran Wakaf Digital dalam Mencapai Tujuan Pembangunan Berkelanjutan (SDG’s) - Auna Nida Ulhusna, Nasya Silmi; Azizah, Nurul; Putri Dinanti, Sevina; Adriansyah, Zidan (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
Waqf as one of the Islamic financial instruments has a strategic role in advancing the welfare of society and contributing to sustainable development. It has a strong relevance to the SDGs. Digital-based waqf is the collection and management of waqf by utilizing technology and digital platforms as an effort to accelerate the transformation of productive waqf so that it can be more effective, efficient, and transparent. Through a descriptive qualitative approach with secondary data from literature study analysis, waqf has an important role in achieving sustainable development through various means. Waqf as a permanent donation for social and religious welfare, supporting education, improving access to healthcare, contributing to economic empowerment through productive waqf, and waqf can fund projects that support environmental preservation. The implementation of digital waqf involves the development of a digital platform that allows donors to conduct waqf online through a website or mobile application. The platform facilitates the donation process, tracking, and reporting on the use of waqf funds. Examples of the application of this technology can be seen in initiatives such as Waqf Chain, which uses blockchain to manage waqf assets.Smart contracts are used to automatically execute waqf agreements. Crowdfunding platforms are also used to raise waqf funds from the wider community, enabling participation from various walks of life. Digital wallets and electronic payment methods are integrated to make it easier for donors to make waqf contributions. However, many people still lack understanding and education about the concept of digital waqf and the benefits that can be derived from it, and tend to be skeptical of the use of new technology in waqf management. Therefore, intensive and continuous education is needed to increase public awareness and participation in digital waqf.